Log Data Analysis of Player Behavior in Tangram Puzzle Learning Game - Rizki Diaz, Ivenulut; Supianto, Ahmad Afif; Tolle, Herman (International Journal of Interactive Mobile Technologies (iJIM), 2018)
Understanding player behavior in a game is quite important to know people model thinking. Through puzzle games, people can train spatial abilities in a geometry lesson. Spatial ability consists of five groups, one of them is perceptual speed. The Perceptual Speed factor is characterized by the speed in finding a configuration in a mess of distracting material. This research purposes to know user behavior in Tangram Puzzle game based on user data log. Analysis user behavior from two aspects: the dominant of first selecting a puzzle pieces and the correlation between the number of puzzle completion with time. And based on this research can be concluded that player will choose a shape that easily to identified and has a larger size than other to be completed first. Whereas the correlation between the number of completion and time is on a moderate level and quite significant.